Experimental and Computational Framework to Design Well-Organized Fibrous Scaffolds for Cardiac Tissue Engineering - Laita Dieste, Nicolas; Martinez Barca, Miguel Angel; Doblaré Castellano, Manuel; Peña Baquedano, Estefanía (Jornada de Jóvenes Investigadores del I3A, 2022)
This study focuses on the design of a ventricular assistant device, consisting of a PCL scaffold filled with a cell laden hydrogel. In order to study its mechanical behaviour, several tests have been carried out on scaffold prototypes and also on cardiac tissue. A computational environment has been developed based on the obteined results.